Origins of minigene-dependent growth inhibition in bacterial cells - Heurgué-Hamard, Valérie (Oxford University Press, 2000)
The expression of very short open reading frames in Escherichia coli can lead to the inhibition of translation and an arrest in cell growth. Inhibition occurs because peptidyl-tRNA hydrolase fails to recycle sufficiently rapidly peptidyl-tRNA released from ribosomes at the stop signal in competition with normal termination, causing starvation for essential species of tRNA. Previous studies have shown that the last sense codon, the strength of the Shine–Dalgarno sequence and the nature and context of the stop codon affect the toxicity associated with mini-gene expression. Here, several important parameters are studied as a function of the length of the mini-gene coding sequence. The rate of peptidyl-tRNA drop-off catalysed by translation factors decreases dramatically for peptides longer than a hexamer. The probability that ribosomes recycle without dissociation of the mini-gene mRNA varies strongly with the length of the coding sequence. The peptidyl-tRNA hydrolase rap mutant, unlike the wild-type enzyme, is highly sensitive to the length and sequence of the peptide. Together, these parameters explain the length dependence of mini-gene toxicity.